Nutritional and microbial safety of common commercial aquafeeds sold in Ogun State, Nigeria - Ojetayo, T.A; Durojaiye, Abiola; Bamidele, N.A; Omotehinse, O.M; Teluwo, S.I (Acta Aquatica: Aquatic Sciences Journal, 2022)
The nutritional and microbial safety of fish feeds were investigated in this study. Commercially available fish feed brands (Eco-float, Skretting, Top-Feeds, Blue Crown) were procured from sales outlets in Ogun State, Nigeria. Moisture ranged from 8.15 to 8.82 and these values were not significantly different (p>0.05) except for Topfeed. Skretting had the highest crude protein value (48.49±0.03) while Ecofloat recorded the least value of 45.30±0.06 (p<0.05). The values obtained for crude fibre, crude fat, ash and carbohydrate were significantly different (p<0.05) across the sampled feeds. Crude fibre ranged from 4.31±0.04 in Ecofloat to 3.20±0.03 in Skretting. Skretting had the highest value recorded for crude fat (6.27±0.11) and ash (10.06±0.18) while Ecofloat had the least value of 1.29±0.00 and 8.01±0.17 respectively. Ecofloat had the highest value for carbohydrate (32.95±0.07), marginally followed by Topfeed (28.79±0.13) and Bluecrown (28.65±0.06) with Skretting recording the lowest value (23.55±0.38). The values for all the minerals analyzed were significantly different (p<0.05). Calcium had the highest values across the sampled feeds, followed by sodium while potassium recorded the lowest values. Tannin recorded the highest value amongst all the phytochemicals, followed by flavonoids and the least value was recorded for glycosides. Total aerobic count, total coliform count and total fungal count ranged from 1.61±0.01 to 3.53±0.0, 0.00±0.00 to 3.10±0.01 and 0.00±0.00 to 2.34±0.05 respectively. Isolated bacteria include Staphylococcus aureus, S. saprophyticus, Klebsiella spp, Bacillus spp and Escherichia coli. Fungi identified were Aspergillus niger, Rhizopus spp, Aspergillus flavus, Geotrichum spp and Saccharomyces spp. Hence, there is need for quality monitoring.Keywords: aquafeed safety, microbial risk, Nigeria